2016
DOI: 10.1089/end.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Reconstruction on Renal Function After Partial Nephrectomy

Abstract: Studies evaluating renal function preservation after partial nephrectomy should control for reconstructive injury in addition to ischemia time and resected healthy margin. Cortical renorrhaphy is associated with renal volume and functional loss on retrospective studies, which might be especially relevant in the setting of chronic kidney disease or solitary kidney. Newer biomarkers of renal injury should be used when studying predictors of renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…In the case of larger tumors, the defect site of the parenchyma by the tumor resection becomes wider and the chance of renorrhaphy increases accordingly. Previous reports have shown that an inadvertent vascular injury by renorrhaphy is the leading cause of pseudoaneurysm and adverse effects on renal function . Therefore, it is ideal to eliminate the chance of carrying out parenchymal renorrhaphy, from the viewpoints of the risk of complications and preservation of renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of larger tumors, the defect site of the parenchyma by the tumor resection becomes wider and the chance of renorrhaphy increases accordingly. Previous reports have shown that an inadvertent vascular injury by renorrhaphy is the leading cause of pseudoaneurysm and adverse effects on renal function . Therefore, it is ideal to eliminate the chance of carrying out parenchymal renorrhaphy, from the viewpoints of the risk of complications and preservation of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In general, parenchymal renorrhaphy is carried out as a standard procedure to prevent hemorrhage and urinary leakage. However, previous reports have shown that an inadvertent vascular injury by renorrhaphy is the leading cause of pseudoaneurysm and adverse effects on renal function . In particular, in the case of larger tumors, as the defect site of the parenchyma by the tumor resection becomes wider, renorrhaphy increases accordingly.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, several series have suggested that another possible option to maximise the preservation of parenchymal volume during PN could be to omit cortical renorrhaphy (i.e. use of only one or two running base layer suture to ligate blood vessels without cortical repair), which has been referred to as the ‘non‐renorrhaphy technique’ . Authors of these series assumed that omitting cortical renorrhaphy could minimise renal volume and functional loss by limiting local ischaemia due to multiple sutures and parenchymal compression used in the sliding‐clip renorrhaphy .…”
Section: Discussionmentioning
confidence: 99%
“…According to these findings, it may be an interesting strategy to perform SAC or OCT to minimize WIT by obtaining a comparatively bloodless surgical view as well as achieving oncological outcome. A variety of techniques such as enucleation [16] or meticulous reconstruction [17] have been introduced to improve renal functional outcomes after PN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies demonstrated no difference in postoperative long-term renal functions between clamping techniques, although postoperative short-term renal function issue remains controversial [7-10]. Selection bias and variety of surgical techniques such as enucleation [16] or omit from renorrhaphy [17] might be taken into accounts for different results. New onset or upstage chronic kidney disease (CKD) has been another concern and not been thoroughly studied [11-14].…”
Section: Introductionmentioning
confidence: 99%